Correlating crystallographic texture with anisotropic properties and sheet metal forming of aluminium alloys - Olaf Engler (Journal of Materials Research and Technology)
The elastic and plastic anisotropy of aluminium wrought alloys is largely controlled by the crystallographic texture of the material, which has developed during the preceding thermomechanical processing. Conversely, texture can be exploited to simulate anisotropic materials properties, typically with the help of crystal-plasticity simulations. The present paper summarizes the author's activities on using texture to simulate anisotropic materials behaviour with the help of the visco-plastic self-consistent (VPSC) scheme. Application possibilities include the prediction of in-plane anisotropy developing during uniaxial and plane strain tensile tests, earing during cup drawing of Al sheet products as well as polycrystal-plasticity driven prediction of input data used to calibrate phenomenological yield functions.Sheet metal forming is commonly simulated with the finite element method (FEM), where anisotropic properties are accounted for by suitable materials models. Notwithstanding that state-of-the-art phenomenological yield functions provide for a high flexibility sufficient to capture the anisotropy of strongly textured materials, the experimental determination of the required calibration parameters is tedious. Rather, the materials parameters needed to calibrate the yield function are derived in a pragmatic and computationally efficient approach with VPSC simulations from texture. The resulting multilevel modelling framework is evaluated against earing simulations which constitute a demanding proof-of-principle for consideration of the anisotropic materials response during FEM forming simulations.